اضطراب الاتصال الاسري وعلاقته ببعض الاضطرابات الشخصية لدى عينة من الحالات السيكوباثية _ الهسيترية _ الاكتائبية باستخدام اختبار مينسوتا متعدد الاوجه - امليك فريدة اسمهان; ديخن فاطمة شهرزاد (جامعة محمد بوضياف -المسيلة, 2025)
ملخص الدراسة : تناولت الدراسة الحالية موضوع اضطراب الاتصال الاسري وعلاقته ببعض اضطرابات الشخصية ( لدى عينة من الحالات الاكتئابية والهيستيرية والسيكوباثية ) باستخدام اختبار مينسوتا متعدد الأوجه ، كدراسة عيادية ، هدفنا من خلالها تسليط الضوء على التواصل الاسري ومساهمته في ظهور الاضطرابات الشخصية ، وباتباع المنهج العيادي لدراسة حالات البحث والتي تمثلت في 3 حالات تظهر عليهم أعراض اضطرابات في الشخصية كما تم استخدام مجموعة من الوسائل والأدوات وهي : المقابلة النصف موجهة ، استبيان الاتصال الاسري ، اختبار مينسوتا متعدد الأوجه ولخصت الدراسة إلى أن : • ان غياب استحضار الصورة الوالدية الابوية (غياب السند التقمصي ) وتفاقم الصورة الامومية غير المناسبة بكفاية , من خلال استجابات للاختبار مينسوتا واستبيان اتصال الاسري و ظهرت كذلك اثناء المقابلات عند 3 حالات , ادى الى خلل في التقمصات , وهاته الوضعية اساسية الملاحظة لانها تشير الى طبيعة الروابط التي تحتاجها الحالات لتجنب الاغتراب النفسي وهاته الاستجابات ماهي الا دفاعات لاشعورية. • استجابة الحالات لمقياس مينسوتا والذي اظهر المقاومة اللاشعورية من خلال النتائج المتحصل ومطابقتها مع المقابلات حيث نلاحظ ميكانزيم الانكار عند الحالة ميم وفاء وميكانيزم المقاومة كرد فعل اللاشعوري .  ان الصورة المثالية للانا عند الحالات والتي ظهرت في مختلف استجابات تعود الى التنشئة الاولية واكتساب المعرفة الخاطئة وهذا ما ادى الى تعزيز السلوكات المضطربة لديهم.  ان اعراض الرهاب الاجتماعي حسب DSM5 لا تتوافق مع اعراض الحالة حيث توافقت مع اعراض الشخصية السيكوباثية حسب DSM5 وهذا ما يثبت صحة الفرضية المقترحة .  ان فرط الحساسية لدى الحالة ماهو الا عرض من اعراض الشخصية الهستيرية وهذا ما ثبت عند دراسة الحالة حسب DSM5 .  ان اعراض الشخصية الاكتئابية تتوافق مع اعراض الحالة حسب DSM5 والذي اثبته اختبار مينسوتا الذي اظهر ارتفاع في مقياس توهم المرض. الكلمات المفتاحية : الاتصال الاسري ، اضطرابات الشخصية ، اختبار مينسوتا متعدد الأوجه ، اضطراب الشخصية الهيستيرية ، اضطراب الشخصية السيكوباثية ، اضطراب الشخصية الاكتئابية The current study addressed the issue of family communication disorder and its relationship to certain personality disorders (in a sample of depressive, hysterical, and psychopathic cases). Using the Minnesota Multiphasic Inventory (MMII) as a clinical study, we aimed to shed light on family communication and its contribution to the emergence of personality disorders. We followed a clinical approach to studying the research cases, which consisted of three cases exhibiting symptoms of personality disorders. A set of tools and methods were also used: a semi-structured interview, a family communication questionnaire, and the Minnesota Multiphasic Inventory (MMII). The study concluded that: The lack of recall of the parental image (lack of empathic support) and the exacerbation of an insufficiently appropriate maternal image, as demonstrated by responses to the Minnesota test and the family communication questionnaire, and also evident during interviews in three cases, led to a defect in empathy. This situation is essential to observe because it indicates the nature of the bonds that the cases need to avoid psychological alienation, and these responses are nothing more than unconscious defenses. • The cases' response to the Minnesota Scale revealed unconscious resistance through the results obtained and their consistency with the interviews. We note the denial mechanism in case Mim Wafaa and the resistance mechanism as an unconscious reaction.  The idealized ego image in the cases, which appeared in various responses, is due to their initial upbringing and the acquisition of false knowledge, which led to the reinforcement of their disturbed behaviors.  The symptoms of social phobia according to the DSM-5 do not correspond to the symptoms of the case, as they coincided with the symptoms of psychopathic personality according to the DSM-5, which confirms the validity of the proposed hypothesis.  The hypersensitivity in the case is merely a symptom of histrionic personality, as confirmed by the case study according to the DSM-5.  The symptoms of depressive personality are consistent with the symptoms of the case according to the DSM-5, as confirmed by the Minnesota Test, which showed an increase in the hypochondriasis scale. Keywords: family communication, personality disorders, Minnesota Multiphasic Inventory, histrionic personality disorder, psychopathic personality disorder, depressive personality disorder